Análise de estruturas reticuladas geometricamente não-lineares com o uso da formulação corrotacional de elementos finitos - Souza, John Williams Ferreira de (2023)
There are several works dedicated to the development of model formulations of lattice structures that take into account the displaced position of the structure, as well as the different nonlinear behaviors inherent to these structures. The tendency to use more slender and stronger structures makes the subject of stability analysis of fundamental importance. This work aims to propose a static analysis and presents of structural models by finite elements, studied to carry out static studies of models structured by finite linear elements with non-linearity by finite elements. To do so, it is necessary to study the concepts of structural analysis, tracing the trajectories of designing the structures, the characteristics of the design of the finite element method, the concepts of non-linearity chosen and also the study of the programming language. The designed algorithms were tested in different situations, in order to control the designation used. Therefore, numerical applications with planar trusses and frames in cases of well-established nonlinear behavior in the literature were analyzed.